Analysis of Influencing Factors Traders' Income Post Relocation to Pariaman People's Market - Fathiah, Fathiah; Liyane, Liyane (Talent: Journal of Economics and Business, 2024)
This research aims to determine the factors that influence traders' income after relocating to the Pariaman people's market. The data in this research was collected through distributing questionnaires, data analysis techniques for street vendors used multiple linear regression analysis, coefficient of determination, and hypothesis testing. The results of the t test research show that the length of business has no effect on the income of street vendors at the Pariaman City People's Market, while location has an effect on the income of street vendors at the Pariaman City People's Market, working hours have an effect on income. Simultaneously shows that length of business, location and working hours simultaneously (together) influence the income of street vendors at the People's Market in Pariaman City.